GPCRs in hypothalamic neurons and their roles in controlling food intake and metabolism - Qiu, Tian; Fu, Ou (Frontiers in Molecular Neuroscience, 2025)
G-protein coupled receptor (GPCR) subtypes within the hypothalamus play a pivotal role in maintaining body homeostasis, particularly in the regulation of food intake and energy metabolism. This review provides an overview of classical loss and gain-of-function studies on GPCRs related to feeding and metabolism, with a focus on emerging cell-type-specific investigations. These studies reveal that diverse GPCR-expressing neuronal populations are intricately linked to feeding and energy balance. We also discuss recent findings that highlight the interaction of distinct peptide-GPCR systems in modulating complex feeding behaviors.